Stabilisation of microalgae: Iodine mobilisation under aerobic and anaerobic conditions. (October 2015) - Han, Wei; Clarke, William; Pratt, Steven
Highlights: First investigation into iodine mobilisation during algae stabilisation. Useful amounts of iodine are retained during aerobic and anaerobic stabilisation. I mobilisation is correlated with C emission, indicating I present as organoiodine. N compared to I mobilisation indicates N and I are housed separately in algae. Abstract: Mobilisation of iodine during microalgae stabilisation was investigated, with the view of assessing the potential of stabilised microalgae as an iodine-rich fertiliser. An iodine-rich waste microalgae (0.35 ± 0.05 mg I g −1 VSadded ) was stabilised under aerobic and anaerobic conditions. Iodine mobilisation was linearly correlated with carbon emission, indicating iodine was in the form of organoiodine. Comparison between iodine and nitrogen mobilisation relative to carbon emission indicated that these elements were, at least in part, housed separately within the cells. After stabilisation, there were 0.22 ± 0.05 and 0.19 ± 0.01 mg g −1 VSadded iodine remaining in the solid in the aerobic and anaerobic processed material respectively, meaning 38 ± 5.0% (aerobic) and 50 ± 8.6% (anaerobic) of the iodine were mobilised, and consequently lost from the material. The iodine content of the stabilised material is comparable to the iodine content of some seaweed fertilisers, and potentially satisfies an efficient I-fertilisation dose.